Regulation by FLOWERING LOCUS T and TERMINAL FLOWER 1 in Flowering Time and Plant Architecture. Issue 4 (21st January 2021) - Liu, Lu; Xuan, Lijie; Jiang, Yupeng; Yu, Hao
Abstract : The conversion from vegetative to inflorescence shoot apical meristem is one of the key developmental switches in flowering plants. This transition is modulated by various environmental and endogenous stimuli and controlled by sophisticated regulatory networks. Regulation of flowering time and inflorescence architecture has a great impact on plant reproductive success and significantly influences plant biomass and fitness. FLOWERING LOCUS T (FT), a mobile protein identified as a major component of florigen, promotes the transition to flowering, whereas its homologous protein TERMINAL FLOWER 1 (TFL1) functions oppositely. Studies in various species reveal that FT and TFL1 play universal and multifaceted roles in a wide range of developmental processes in plants. Hence, modulations of FT/TFL1 and their regulatory pathways have a considerable impact on plant development and crop domestication. Herein, an overview of the molecular basis underlying the regulation of FT/TFL1 expression and modulation of their protein trafficking and the relevant mechanisms in flowering time control and meristem development is provided. Whenever applicable, their functional conservation and divergence in various plant species are also discussed. Abstract : FLOWERING LOCUS T (FT) and TERMINAL FLOWER 1 (TFL1) belong to the phosphatidylethanolamine‐binding protein family. They play antagonistic roles in determining flowering time and inflorescence architecture and are potential molecular markers for plant breeding. Herein, the molecular basis underlying the regulation of FT / TFL1 expression and modulation of their protein trafficking as well as the relevant mechanisms in plant development are summarized.